2013
DOI: 10.1002/gcc.22123
|View full text |Cite
|
Sign up to set email alerts
|

Complex karyotype in mantle cell lymphoma is a strong prognostic factor for the time to treatment and overall survival, independent of the MCL international prognostic index

Abstract: Mantle cell lymphoma (MCL) is usually an aggressive disease. However, a few patients do have an "indolent" evolution (iMCL) defined by a long survival time without intensive therapy. Many studies highlight the prognostic role of additional genetic abnormalities, but these abnormalities are not routinely tested for and do not yet influence the treatment decision. We aimed to evaluate the prognostic impact of these additional abnormalities detected by conventional cytogenetic testing, as well as their relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 36 publications
1
34
0
6
Order By: Relevance
“…10,12,13,15 Espinet et al described loss(17p) as being prognostic in a multivariable model, 9 and Sarkozy et al reported that it was prognostic in univariable but not multivariable modeling. 12 More recently, Eskelund et al used data from the Nordic MCL trials to demonstrate that in patients aged <66 years, TP53 mutations were associated with inferior OS (HR, 6.2; P<.01) and time to disease recurrence (HR, 6.9; P<.01), with a median OS of 1.8 years. 16 In addition, they demonstrated that TP53-mutated cases had an inferior response to intensive induction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,13,15 Espinet et al described loss(17p) as being prognostic in a multivariable model, 9 and Sarkozy et al reported that it was prognostic in univariable but not multivariable modeling. 12 More recently, Eskelund et al used data from the Nordic MCL trials to demonstrate that in patients aged <66 years, TP53 mutations were associated with inferior OS (HR, 6.2; P<.01) and time to disease recurrence (HR, 6.9; P<.01), with a median OS of 1.8 years. 16 In addition, they demonstrated that TP53-mutated cases had an inferior response to intensive induction therapy.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 ‐mutated MCL patients generally have a poor prognosis and have a poor response to standard frontline chemoimmunotherapy . Patients with a complex karyotype, defined as having three or more chromosomal abnormalities in addition to t(11;14) or additional chromosomal abnormalities detected by array CGH (comparative genomic hybridization) generally have poorer outcomes …”
Section: Advances In MCL Prognosticationmentioning
confidence: 99%
“…Given this heterogeneity and the limited discriminatory power of the International Prognostic Index (IPI), the simplified MCL IPI (sMIPI) including age, performance status, white blood cell counts, and lactate dehydrogenase (LDH) level enables assessment of the prognosis of individual patients. As sMIPI was developed from patients with advanced stage disease in the pre‐rituximab era, and the variables of sMIPI were just a reflection of tumor burden and serve as indirect markers for the biological characteristics of MCL, many other prognostic factors were analyzed such as Ki‐67, TP53, stage, serum β2‐microglobulin, chromosome karyotype, and other parameters . Unfortunately, little research into MCL took the host immunity and tumor microenvironment into account.…”
mentioning
confidence: 99%
“…As sMIPI was developed from patients with advanced stage disease in the pre-rituximab era, (3) and the variables of sMIPI were just a reflection of tumor burden and serve as indirect markers for the biological characteristics of MCL, many other prognostic factors were analyzed such as Ki-67, TP53, stage, serum b2-microglobulin, chromosome karyotype, and other parameters. (1,3,4) Unfortunately, little research into MCL took the host immunity and tumor microenvironment into account. More and more evidence has proved the interaction among lymphoma cells, stromal cells, and immune cells.…”
mentioning
confidence: 99%